Characteristics of Concrete with the Addition of Fabric Waste as Fibers on the Compressive and Flexural Strength of Concrete - Latifha Sari, Nadjwa; Mustakim; Kasmaida (Journal of Civil Engineering and Planning (JCEP), 2024)
Mineral waste, particularly from synthetic fabrics, is challenging to manage due to its non-decomposable nature and inability to compost. This waste accumulates, posing environmental risks. As a solution, utilizing fabric waste in concrete mixtures has been proposed. This study aims to evaluate the compressive strength and stiffness of concrete with added fabric waste and identify the optimal percentage of waste as fiber reinforcement. The research employed experimental methods following the SNI-03-2834-2000 standard at the Structural Materials Laboratory, Muhammadiyah University of Parepare, conducted from February to March 2024. Results showed that on the 28th day, adding 5% table iron increased concrete compressive strength to 9.91 MPa, while increasing it to 10% reduced strength to 0.66 MPa. Adding 10% cotton fabric improved compressive strength by 2.23 MPa and flexural strength by 3.822 MPa. The findings suggest that fabric waste, combined with vibration and wire reinforcement, enhances concrete performance. The optimal results were observed with 5% boron material for compressive strength and 10% cotton material for flexural strength, demonstrating the potential of textile waste as an effective concrete mixture component. This study highlights the dual benefits of waste reduction and material enhancement, contributing to environmental sustainability and advancing concrete technology.